Product of the Generalized L-Subgroups - Dilek Bayrak; Sultan Yamak (Journal of Mathematics)
We introduce the notion of (λ,μ)-product of L-subsets. We give a necessary and sufficient condition for (λ,μ)-L-subgroup of a product of groups to be (λ,μ)-product of (λ,μ)-L-subgroups.